Trends of Moisture and Electrical Conductivity in Clay Liners - Muawia Dafalla; Ahmed Al-Mahbashi; Mosleh Al-Shamrani (Geofluids)
This research is aimed at investigating the influence of ambient air temperature on the moisture content and electrical conductivity of clay sand mixtures. Volume changes as a result of shrinking or swelling are very much related to the moisture content and the electrical conductivity for liners consisting of sand and clays. The laboratory tests carried out for clay sand mixtures subjected to drying indicated a bilinear trend for 15, 20, 25, and 30% clay content. Moisture content measurements are influenced by the ambient temperature and exposure time. Watering a clay sand layer at a regular frequency in a field site revealed useful information on the trends of moisture gain and loss. Suction fluctuation associated with these changes is responsible for absorbing variable amounts of water. Moisture/Temp/EC sensors (5TE) were utilized to survey a sand clay liner section over 30 day’s period. A metrological station installed within the site was used to observe temperature, humidity, and rain fall. The drop of moisture and electrical conductivity was found to be nonlinear with temperature changes and reflecting the bimodal nature of the soil. The general trends of repeated wetting and drying were found similar in shape.